Effects of Recharge and Discharge on δ2H and δ18O Composition and Chloride Concentration of High Arsenic/Fluoride Groundwater from the Datong Basin, Northern China. (1st February 2013) - Xie, Xianjun; Wang, Yanxin; Su, Chunli; Duan, Mengyu
Abstract : To better understand the effects of recharge and discharge on the hydrogeochemistry of high levels of arsenic (As) and fluoride (F) in groundwater, environmental isotopic composition (δ 2 H and δ 18 O) and chloride (Cl) concentrations were analyzed in 29 groundwater samples collected from the Datong Basin. High arsenic groundwater samples (As > 50 μg/L) were found to be enriched in lighter isotopic composition that ranged from −92 to −78 ‰ for deuterium (δ 2 H) and from −12.5 to −9.9 ‰ for oxygen‐18 (δ 18 O). High F‐containing groundwater (F > 1 mg/L) was relatively enriched in heavier isotopic composition and varied from −90 to −57 ‰ and from −12.2 to −6.7 ‰ for δ 2 H and δ 18 O, respectively. High chloride concentrations and δ 18 O values were primarily measured in groundwater samples from the northern and southwestern portions of the study area, indicating the effect of evaporation on groundwater. The observation of relatively homogenized and low δ 18 O values and chloride concentrations in groundwater samples from central part of the Datong Basin might be a result of fast recharge by irrigation returns, which suggests that irrigation using arsenic‐contaminated groundwater affected the occurrence of high arsenic‐containing groundwater in the basin.